Applying Lean Hospital Strategies to Minimise Waiting Times in the Internal Medicine Clinic - Ilham Ahmadi; Erry Yudhya Mulyani; Anastina Tahjoo (International Journal of Economics, Commerce, and Management, 2026)
Prolonged outpatient waiting time remains a major challenge in public hospitals and reflects inefficiencies in service process management. Internal medicine clinics are characterised by high service complexity and patient volume, making them particularly vulnerable to process waste that contributes to extended waiting times. Objective: This study aimed to develop an outpatient service flow model based on the Lean Hospital approach to reduce waiting time in the internal medicine clinic of RSUD Balaraja. Methods: A qualitative case study design was employed. Data were collected through direct observation of outpatient service processes, document review, and Focus Group Discussions (FGD) with relevant stakeholders. Process analysis was conducted using Value Stream Mapping (VSM) to identify value-added and non–value-added activities, while Fishbone Diagram analysis was applied to explore the root causes of process inefficiencies. All findings were integrated to develop a future-state outpatient service flow model. Results: The findings indicate that prolonged outpatient waiting time is primarily influenced by inefficient service flow design, repetitive administrative processes, and weak coordination among service units. The proposed service flow model demonstrates a more streamlined, integrated, and patient-centred process, with potential reductions in waiting time through systematic waste elimination and process improvement. Conclusion: The Lean Hospital approach provides an effective framework for developing outpatient service flow models in public hospitals. The proposed model offers a practical basis for improving outpatient service efficiency in complex clinical settings such as internal medicine clinics.